Survey on Neuro-Fuzzy Based Single Phase Multi-Level Inverters Using FPGA - Ahamed Z, Ameer; Jain, Anuj (International Journal of Engineering and Technology, 2018)
In the Power electronic converters harmonic reductions is the main issue which will affect the power factor which intern affects power quality. The multi-level inverters here studied the inverter switches strategy is controlled by FPGA technique and the space vectors are assigned using the NN strategy, a survey is made on different types of multi-level inverters which is controlled using FPGA and NN. In this paper a survey is done on Multi level inverters using different control techniques to know how far FPGA and NN is better in performance for power electronic applications.Â Â